THD reduction in novel asymmetrical 21 level MLI using FLO-MOA algorithm optimized cascaded controller technique - Mohandas Ramaiah; Bharath Vaniyambadi Sathyanarayanan (Institute of Advanced Engineering and Science, 2026)
Since multi-level inverters (MLIs) may operate at lower switching frequencies and reduce switching losses, they are frequently used in high and medium electric drives for renewable energy applications. Lower-order harmonics could result from using a lower switching frequency, which would increase line current distortion. MLIs provide fewer output harmonics than traditional converters. This research suggested a hybrid strategy for creating a 21-level MLI. The suggested cascaded fractional-order tilt integral fractional-order proportional tilt derivative (FOTI-FOPTID) controller is used to adjust the switching pulse for the 21-level MLI. In this work, the Mother Optimization algorithm (MOA) is combined with the Frilled Lizard optimization (FLO) method to improve it. This results in the FLO-MOA algorithm, which is used to adjust the controller's gain parameters. This strategy reduces the number of switches and asymmetrical sources of dc voltage. The inverter's efficiency is raised, power loss is minimized, total harmonic distortion (THD) is decreased, and output voltage levels are improved.